Scholarly practices and inquiry in the preparation of mathematics teachers - Mewborn, Denise S.; Lee, Hollylynne S. (Emerald Publishing Limited, 2014)
(Orginally published in 2009)The sixth monograph of AMTE highlights examples of the important scholarship of the mathematics teacher education community. This monograph, like others produced by AMTE, serves as a forum for mathematics teacher educators to exchange ideas, experiences, resources, and detailed acounts of work to improve preservice and inservice teacher preparation. Chapters address important issues such as: designing tasks to emphasize mathematics knowledge for teaching; capitalizing on opportunities for student teaching mentor learning; and learning to lead classroom mathematics discussions.
Includes index.
Keywords: Mathematics teachers -- Training of -- United States.; Mathematics -- Study and teaching -- United States.; Student teachers.; Education -- Professional Development.; Educational strategies and policy.; Teacher training.; elektronické knihy; electronic books